The Role of Forest Experiences in Enhancing Child Well-being and Resilience - M. Kobler, Evelyn (Revija za elementarno izobraževanje, 2025)
Given the alarming prevalence of (mental) health problems in children and young people, exacerbated by the pandemic and environmental fears, the question of how we can strengthen children for an increasingly complex world with all that it entails is more topical than ever. This article therefore addresses the importance of resilience, well-being, and experience of nature for children’s development, particularly through time spent in a forest. Experiencing the forest strengthens the immune system, reduces stress, and promotes social and motor skills, and can therefore have a positive influence on children’s well-being and the development of resilience.
Keywords: child well-being, resilience, forest experiences, forest-based education.